Forest management and root systems in changing climatic conditions - Finér, Leena; Ohashi, Mizue; Hirano, Yasuhiro; Repo, Tapani (Taylor & Francis, 2025)
Climate change increases air and soil temperatures and the frequency of extreme weather events such as high temperatures, droughts, and flooding. These changes negatively impact forest ecosystems and the provision of ecosystem services such as timber supply and carbon sequestration. Fine roots and associated mycorrhizae play an essential role in the functioning of forest ecosystems because they absorb water and nutrients from the soil and owing to their short lifespan, significant amounts of carbon and nutrients are transferred through them into the soil. Here, we reviewed the existing literature on the responses of tree fine roots and root systems to increasing soil temperature and changes in soil water availability and waterlogging. We also discussed how the negative responses of fine roots to environmental changes can be mitigated in forest management operations by selecting tree species and provenances, growing mixed tree species stands, carrying out continuous-cover forestry, and avoiding rutting and soil compaction when using forest vehicles. Our main focus is on the root systems of boreal and temperate forests. Knowledge of root responses to changing environmental conditions and different management practices, which could be used to mitigate negative effects, is still very limited and requires more research and development before they can be introduced in practice.
Keywords: jatkuva kasvatus; sekametsät; juuret; lämpötila; kosteus; metsämaa